Hadith #1064 - Sahih Muslim - Ibrahim bin 'Abdul 'Aziz bin 'bdul Malik إبراهيم بن عبد العزيز بن عبد الملك (Sahih Muslim)
I used to read the Qur’an with my father in the vestibule (before the door of the mosque). When I recited the ayat (verses) concerning prostration, he prostrated himself. I said to him: Father, do you prostrate yourself in the path? He said: I heard Abu Dharr saying: I asked the Messenger of Allah (ﷺ) about the mosque that was first set up on the earth. He said: Masjid Harim. I said: Then which next? He said: The Masjid al-Aqsa. I said: How long is the space of time between the two? He said:
Grade: Sahih

Hadith #1183 - Sahih Muslim - Ibrahim bin 'Abdul 'Aziz bin 'bdul Malik إبراهيم بن عبد العزيز بن عبد الملك (Sahih Muslim)
‘Alqama led us in the noon prayer and be offered five rak’ahs; when the prayer was complete, the people said to him: Abu Shibl, you have offered five rak’ahs. He said: No, I have not done that. They said: Yes (you said five rak’ahs). He (the narrator) said: And I was sitting in a corner among people and I was just a boy. I (also) said: Yes, you have offered five (rak’ahs). He said to me: O, one-eyed, do you say the same thing? I said: Yes. Upon this he turned (his face) and performed t
Grade: Sahih

Hadith #5057 - Sahih Muslim - Ibrahim bin 'Abdul 'Aziz bin 'bdul Malik إبراهيم بن عبد العزيز بن عبد الملك (Sahih Muslim)
I was sitting with Ibn ‘Umar when a man came to him, and said: Did Allah’s Messenger (ﷺ) forbid the preparation of Nabidh in a green pitcher (besmeared with pitch), in varnished jar and in gourd? Thereupon he said: Yes.
Grade: Sahih

Hadith #5633 - Sahih Muslim - Ibrahim bin 'Abdul 'Aziz bin 'bdul Malik إبراهيم بن عبد العزيز بن عبد الملك (Sahih Muslim)
Usama b. Zaid and Sa’d had been sitting and they had been conversing and they said this hadith.
Grade: Sahih

Hadith #7424 - Sahih Muslim - Ibrahim bin 'Abdul 'Aziz bin 'bdul Malik إبراهيم بن عبد العزيز بن عبد الملك (Sahih Muslim)
‘I have fifty thousand Ḥadīth on authority of the Prophet, peace and blessings upon him’.
Grade: Sahih